Theoretical models for structural phase transitions in molecular clusters and crystals of inorganic compounds - Grebenyuk, A.G. (Functional Materials, 2004)
The modern theoretical approaches to investigation of polymorphism and structure phase transitions in inorganic compounds are reviewed. The emphasis is made on new ideas of solid state thermodynamics, structure and energy simulation of polymorphs, and results of application thereof to simple substances and binary compounds. Статья содержит обзор современных теоретических подходов к исследованию полиморфизма и структурных фазовых переходов неорганических соединений. Основное внимание уделено новым идеям в термодинамике твердого тела, методам моделирования структуры и энергетики полиморфных форм и результаты их применения к простым веществам и бинарным соединениям. Стаття містить огляд сучасних теоретичних підходів до дослідження поліморфізму та структурних фазових переходів неорганічних сполук. Основну увагу приділено новим ідеям у термодинаміці твердого тіла, методам моделювання структури і енергетики поліморфних форм та результатам їхнього застосування до простих речовин і бінарних сполук.